2005
DOI: 10.1177/1541204005278677
|View full text |Cite
|
Sign up to set email alerts
|

An Application of Fear Appeal Messages to Enhance the Benefits of a Jail Encounter Program for Youthful Offenders

Abstract: Research has consistently shown that so-called scared straight types of jail encounter programs do not have positive benefits for youthful offenders. However, few if any inmate-youth encounter programs have utilized the results of fear appeals message research. Results of the present study suggest that an inmate-youth encounter program may lead to attitude change in youthful offenders if components of successful fear appeals are incorporated into the program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Topics addressed through application of the EPPM include hearing loss; [45] vaccine risk; [46] farm hazards; [47] general health promotion; [28] risk behaviors; [48] breast self-exams; [29] alcohol warnings; [30] firearms; [31] drinking water; [32] terror management; [49] eating disorders; [50] rape; [51] cardiovascular disease; [33] genetic testing and tobacco use; [34] burn prevention; [35] road safety; [36] and jail encounter programs. [52] The results of this research add hearing loss prevention in college students to this list of populations who have benefitted from application of the EPPM to health hazards that they face.…”
Section: Practical Applicationsmentioning
confidence: 94%
“…Topics addressed through application of the EPPM include hearing loss; [45] vaccine risk; [46] farm hazards; [47] general health promotion; [28] risk behaviors; [48] breast self-exams; [29] alcohol warnings; [30] firearms; [31] drinking water; [32] terror management; [49] eating disorders; [50] rape; [51] cardiovascular disease; [33] genetic testing and tobacco use; [34] burn prevention; [35] road safety; [36] and jail encounter programs. [52] The results of this research add hearing loss prevention in college students to this list of populations who have benefitted from application of the EPPM to health hazards that they face.…”
Section: Practical Applicationsmentioning
confidence: 94%
“…Two articles discussed a related “experiment” (Blunkett 2008; Wilson and Groombridge 2010), but upon further examination these studies did not use experimental methods or eligible outcomes. Another positive descriptive report was identified of a juvenile awareness program involving ‘fear appeal messages’ (Windell and Allen 2005), but no evaluative data were provided. Thus, no new evaluations were identified for inclusion.…”
Section: Methods Of the Reviewmentioning
confidence: 99%
“…An evaluation of a "Scared Straight" program for truants (as discussed in the previous section) was discovered, but this study was excluded as it did not involve randomization (Bazemore et al 2004). Another positive descriptive report was identified of a juvenile awareness program involving 'fear appeal messages' (Windell and Allen 2005), but no evaluative data were provided. A more recent systematic review (Klenowski et al 2010) was found that included narrative descriptions of 10 studies, but it identified no new studies eligible for inclusion here.…”
Section: Selection Of Trials Update (2012)mentioning
confidence: 99%